Anxiety and depression in pregnancy: a comparative study between early and late adolescents - Pereira, Alanna Batalha; Mendonça Silva, Flor de Maria Araujo; Figueredo, Eduardo Durans (Journal of Health & Biological Sciences, 2018)
Objective: To study anxiety and depression in pregnant adolescents. Methods: Cross-sectional study in which the Hospital Anxiety and Depression Scale (HADS) was used to evaluate the level of anxiety and depression among patients. The Beck Depression Inventory (BDI), which aims to measure the presence and severity of depression was also applied. 87 pregnant adolescents attended at a prenatal outpatient clinic of a public hospital participated in the study. They were divided into two groups: precocious adolescents (12 to 14 years of age) and late adolescents (15 to 19 years of age). The difference between the means was analyzed using the Student’s t test. A value of p<0.05 was considered significant. Results: In relation to depression, the mean BDI score among the 23 precocious adolescents was 24.5, whereas among the 64 late adolescents, the same score presented a mean of 15.7 (p<0.001). According to the HADS, the precocious pregnant adolescents obtained an average of 8.9 (possible depression), whereas the late pregnant adolescents presented an average of 6.9 (unlikely depression) (p=0.008). Conclusions: Depression was more intense among precocious adolescents than among late adolescents. There was no significant difference in the intensity of anxiety, assessed by the HADS, between precocious and late adolescents.